KONSEP DAN DASAR KEUANGAN DALAM ISLAM - Rizal Darwis (TAHKIM, 2013)
Economic globalization as a legitimate child of the capitalist economy is believed does not able to provide prosperity for all people. This fact is born out of the basic vision of the capitalist economy is not shared prosperity but the economic domination by the capital owners, so what happens is that the rich become the richer and the poor become the poorer. Starting from the phenomenon around 1997's, the economists began to look at the economics practices based on sharia as practiced by the Prophet saw. The economic practices applied by the Prophet is started from the sources of Islam, namely the Qur'an. This paper describes on the concept of financial institutions in the Islamic history, concepts and basics of finance in Islam. Keywords: financial institutions, the basic concept of Islam